Eficiencia de un sistema de lodos activados en el tratamiento de aguas residuales en la industria láctea de Cajamarca - Acosta Sánchez, Luis Alberto (2009)
This present work deals with the efficiency of an activated mud system to treat wastewater from Huacariz SRL Company of Cajamarca and proposes a treatment to remove biochemical oxygen demand DBO5 efficiently. We had four plastic biorreactores of ten liters of capacity that were homogenously in constant form by ten days to obtain active mud. In this process part of fat was and the active mud was eliminated and the active mud was preserved in Erlemeyers in which aliquot of new remainder were added to conserve and to acclimate them. Most of these mud contained yeast and estreptococcuss gram positive. The beginning of the process lasted four days and the first day active mud was added each reactor, staying the ventilation constant; at the end of the process we obtained the output parameter of biochemical demand of oxygen (DBO5). The march of the process was repeated sixteen times obtained an efficiency of 80% of removal of the DBO5. The obtained results we confirmed that the treatment that was used is within the effective allowed regulations.